High-Level Resistance to Ceftazidime Conferred by a Novel Enzyme, CTX-M-32, Derived from CTX-M-1 through a Single Asp240-Gly Substitution - Cartelle, Monica (American Society for Microbiology, 2004)
A clinical strain of Escherichia coli isolated from pleural liquid with high levels of resistance to cefotaxime, ceftazidime, and aztreonam harbors a novel CTX-M gene (bla(CTX-M-32)) whose amino acid sequence differs from that of CTX-M-1 by a single Asp240-Gly substitution. Moreover, by site-directed mutagenesis we demonstrated that this replacement is a key event in ceftazidime hydrolysis